Mutagenesis of the human IgA1 heavy chain tailpiece that prevents dimer assembly. - Atkin, J; Pleass, R; Owens, R; Woof, J (1996)
The structural features of the human IgA1 tailpiece required for interaction with J chain in IgA dimer assembly were investigated using a protein engineering approach. Wild-type and mutant forms of IgA1 were expressed in the mouse myeloma cell line, J558L, which endogenously expresses J chain. Wild-type IgA1 was secreted as a mixture of dimers and monomers. Deletion of the entire tailpiece by stop codon introduction completely prevented dimer formation. Similarly, substitution of the penultimate residue of the tailpiece, Cys471, with serine resulted in the secretion of IgA monomers alone. Substitution of Asn459 with alanine to prevent attachment of N-linked carbohydrate to the tailpiece also resulted in markedly reduced dimer assembly. These results indicate the critical role played by the tailpiece, and Cys471 in particular, in IgA dimerization. In addition, we found tailpiece-deleted IgA1 and the Cys to Ser471 mutant IgA1 were secreted as mixtures of covalently associated monomers (alpha 2L2) and alpha L half-molecules. The tailpiece may thus play some role in promoting the association of alpha-chains required for IgA monomer assembly.